Islamicity Performance Index di Era ESG: Konvergensi, Kompetisi, atau Kesenjangan dalam Pelaporan Keberlanjutan Syariah? - Delia Zara Zaneta; Mukhtaruddin Mukhtaruddin (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
This research is conducted to systematically examine and conceptualize the relationship betweenthe Islamicity Performance Index (IPI) and the Environmental, Social, and Governance (ESG)framework within the domain of Islamic sustainability reporting.The analysis is structuredaround three analytical lenses, namely convergence, competition, and gap. The method employedis a literature review of national and international journals relevant to the topics of IPI and ESG.The findings reveal that the dominant relationship between IPI and ESG is a structural gap.Convergence occurs partially on the social and governance dimensions, competition emerges atthe epistemological level due to differences in value foundations, while the gap occurscomprehensively as both frameworks are fundamentally designed to answer different questions.These findings imply the urgency of developing an integrative Islamic sustainability reportingframework rooted in maqashid syariah.